Evaluation of the behavior of some trees and shrubs under two planting distances - Martinez, Leonardo Antonio; Navia, Jorge Fernando (Revista de Ciencias Agrícolas, 2011)
This study was conducted at the research center FEDEPAPA, municipality of Pasto, Narino, located 1 ° 13 'North latitude and 77 ° 16' west longitude. The objective of this research was the development and initial evaluation of live fences to divide pastures, with five arboreal and shrub species, which were measured for the initial trend of survival, growth, increased stem thickness and number of sprouts; of species Retamo Ulex europaeus, Quillotocto Tecoma stans, Chilca Bacharis latifolia, Acacia decurrens and Aliso Alnus jurullensis, two planting distances of 0.5 and 1m. Analysis of the results reported the largest increase in average final height, was presented with Acacia decurrens 110.24 cm to 1 m to 0.5 m and 101.17cm away Ulex europaeus and with an average of 40 to 45 cm for the two distances seed, while Tecoma stans, Bacharis latifolia and Alnus jorullensis and were the lowest average increase in final height of 30 to 40 cm distances for the two seed respectively. It was also noted that there were no differences between the two sowing distances (0.5 m and 1 m) and concluded that Acacia decurrens and Ulex europaeus are the most recommended consequences for the implementation of live fences as a division of pasture in the highlands Narino.